Normograms of ovarian volume, Uterine size and endometrial thickness in urban midlife Malaysia women - Adeeb N,; Nur-Azurah AG,; Ong FB,; Shamsuddin K,; Seri SS,; Noor-Aini MY, (Penerbit UKM, 2007)
Cancers of the ovary and corpus uteri afflict 5% and 3.6% Malaysian women respectively. Ovarian cancer (OC) remained the deadliest gynaecological malignancy in perimenopausal women mainly due to the lack of symptoms until the disease had spread. Ultrasonography could provide a preliminary screening allowing the clinician to tailor subsequent management and counselling for these women. To support the basis for selective screening, a study on 517 urban disease free women aged 45 years and above, uterus-intact, non-users of HRT was undertaken. This study presented normograms of ovary, uterus and endometrium derived from entry ultrasound assessment. The sample comprised of 58.0% premenopaused and 42.0% postmenopaused women with an average age of 51.27±5.35 years old. Over two thirds were Chinese followed by Malays and Indians. The findings indicated that the average uterine size and endometrial thickness (ET) was 7.21±1.67x4.36±1.30cm and 6.36±3.73mm respectively. Premenopausal women had larger uterus compared to those postmenopaused (p<0.0005) and atrophy of the uterus with age and menopause was demonstrable regardless of ethnicity. Likewise, mean ET in the premenopaused was thicker than the postmenopaused (p<0.0005), showing a gradual decrease with age. Early postmenopausal women demonstrated ET of <5mm, eventually reaching 2mm in women >70 years old. From these findings, a cut-off of <5.0mm was considered clinically acceptable in normal postmenopaused regardless of ethnicity. Nearly one fifth (18.9%) had uterine fibroids, a quarter (25%) in premenopausal women as compared to 10% postmenopaused (p<0.0005). The mean right and left ovarian volume (OV) was 5.48±7.85cm3 and 5.80±16.78cm3 respectively. There was a gradual decline in OV with age and menopause from about 7cm3 at age 45-49 years to less than 1.5cm3 at 70 years giving a clinical norm OV of <7.5cm3 and <3.5cm3 respectively in pre and postmenopausal Malaysian women. Benign ovarian cysts seen in 2.9% had a mean size of 65.14±88.22cm3. In conclusion, ET and OV normograms should be made available for the Malaysian population to facilitate screening for gynaecological malignancies